Poverty, Disputes, and Access to Justice in Two Indonesian Provinces - Cuesta, José; Madrigal, Lucia; Skoufias, Emmanuel (Taylor and Francis, 2018)
This analysis explores the determinants behind the unequal access to justice services among poor Indonesians. The study analyzes the stock of observed past disputes by socioeconomic group and the demand for conflict resolution services for unresolved conflicts or “trajectories.” It also models the hypothetical demand of justice services for future disputes. Results suggest that unequal access to justice might go beyond the financial costs of seeking justice and also depends on individual preferences and community infrastructure. These findings warn against focusing exclusively on formal justice costs to improve the equal access of the poor to conflict resolution services.